Cryptographic Random Number Generator for Mobile Devices - Ozkaynak, Fatih; Ozdemir, Halil Ibrahim; Ozer, Ahmet Bedri (Ieee, 2015)
Different security tools are needed for the security of mobile devices. Random number generators are an important tool for security applications. In this paper, a robust true random number generator algorithm has been proposed for mobile devices. An application of the algorithm is shown in two-level authentication application. Security analysis shows that proposed algorithm has good performance characteristics.
Mobil Cihazlar için Kriptografik Rasgele Sayi Üreteci
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: random number generator; entropy source; two-level authentication